2016
DOI: 10.1016/j.cub.2015.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Cell Competition Drives the Formation of Metastatic Tumors in a Drosophila Model of Epithelial Tumor Formation

Abstract: Cell competition is a homeostatic process in which proliferating cells compete for survival. Elimination of otherwise normal healthy cells through competition is important during development and has recently been shown to contribute to maintaining tissue health during organismal aging. The mechanisms that allow for ongoing cell competition during adult life could, in principle, contribute to tumorigenesis. However, direct evidence supporting this hypothesis has been lacking. Here, we provide evidence that cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 44 publications
(54 reference statements)
3
84
1
Order By: Relevance
“…Eichenlaub et al [61] used a D. melanogaster model of epithelial tumour formation to show that overexpression of both epidermal growth factor receptor (EGFR) and miR-8 in wing imaginal disc cells results in supercompetitive cells that engulf those surrounding them. These supercompetitive cells drive tumourigenesis and metastasis, whereas cells overexpressing either EGFR or miR-8 alone do not.…”
Section: Subclonal Interactions In Heterogeneous Tumoursmentioning
confidence: 99%
“…Eichenlaub et al [61] used a D. melanogaster model of epithelial tumour formation to show that overexpression of both epidermal growth factor receptor (EGFR) and miR-8 in wing imaginal disc cells results in supercompetitive cells that engulf those surrounding them. These supercompetitive cells drive tumourigenesis and metastasis, whereas cells overexpressing either EGFR or miR-8 alone do not.…”
Section: Subclonal Interactions In Heterogeneous Tumoursmentioning
confidence: 99%
“…In this context, supercompetitor mutations may act like 'driver' mutations, which provide a slight competitive advantage to a clonal population within the tumor [93] ( Figure 4C). Recently it was shown that competition within clones/domains overexpressing EGFR and the microRNA mir8 was required for metastasis in the fly imaginal disc [94]. In this situation, the spontaneous variability of downstream effectors between clonal cells (e.g., Myc levels) is probably driving competition.…”
Section: Correction Of Developmental Errors and Agingmentioning
confidence: 99%
“…Similarly, cell competition may also occur within the tumor in mammals as a result of spontaneous variability of protein levels and/or the diversity of genetic background. The elimination of the less-competitive cells may promote the expansion of drug-resistant subpopulations during cancer treatment [88] or the selection of invasive populations [94].…”
Section: Correction Of Developmental Errors and Agingmentioning
confidence: 99%
“…The overgrowing EGFR+miR8 clones induce cell death in nearby wild type cells. However, EGFR+mir8 clones cannot expand through cells that have higher Myc levels, showing that these tumors are susceptible to suppression by competition, and might use competition themselves to expand through wild type cells [47]. …”
Section: Cell Competition and Cancermentioning
confidence: 99%